Binary image steganography method based on layered embedding - Yuxiang CHENG; Weiming ZHANG; Weixiang LI; Nenghai YU (网络与信息安全学报)
A non-additive distortion binary image steganography method was proposed which divided the cover image into two sub cover images, updated the distortion through delivering influence factor, and used the minimizing distortion codes to achieve message embedding.Compared with the previous additive distortion steganography methods with fixed distortion, the proposed method combined the characteristics of binary images with only black and white pixels.Hence, it facilitated the correlation capture of pixel points and dynamic modification of distortion, improving the visual quality and steganography security of the binary image steganography.